Remarks on Communes of the Polish People: the character of organization, the ideology, the meaning - Kuligowski, Piotr (Journal of Education Culture and Society, 2020)
The aim of this paper is to rethink three important issues that refer to Communes of the Polish People’s history. Firstly, it proposes a new understanding of organization frames, in which this group acted, using the Eric Hobsbawm’s term labour sects. Secondly, the intention is to undermine the understanding of the ideological development of this organization through the prism of theoretical activity of Stanisław Worcell and Zenon Świętosławski. In this case it proposes to show Communes of the Polish People in the context of changing of Polish political vocabulary in the 1830s and 1840s using the Reinhardt Koselleck’s term Sattelzeit. In this case the most durable achievement of Communes is invention of the term “Poland of the People” (Polska Ludowa). And thirdly, the article shows that references to Communes became extinct in the 1880s, at the time of the twilight of Romanticism.